Pengembangan Alat Ukur Preferensi Perilaku Agresif Generasi Alpha - Rosa Imani Khan; Widi Wulansari; Imroatus Sholihah (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
Aggressive behavior preferences need to be known from the beginning because they are the root of the emergence of cases of adolescent aggressiveness. Generation Alpha's aggressive behavior preferences need to be known to control and prevent individuals from growing up with harmful aggressive behavior. This study aims to develop a measurement tool for the aggressive behavior preferences of Generation Alpha which is used as a tool to measure the aggressive behavior preferences of children to adolescents today who belong to Generation Alpha. The subjects in this study were 136 Generation Alpha aged 11-12 years. Generation Alpha's aggressive behavior preferences were measured using a closed questionnaire containing Likert scale statements. The research was conducted in June-August 2023. The development stage/procedure uses the Borg & Gall model with simplification into six stages, namely the Information Gathering Stage, Planning Stage, Model Development Stage, Limited Group Trial, Product Revision, and Product Finalization. The conclusion of this study: content validity testing conducted by 5 experts (expert judgment) shows the results that all statement items in this measuring instrument are relevant to the Alpha Generation aggressive behavior preference indicators so that it can be tested as a criterion validity testing stage. The results of the criterion validity test on 136 respondents showed that there were 5 invalid statement items. The total number of items that are empirically declared valid and reliable is 43 items with a reliability value using the Cronbach's Alpha formula of 0.877.Keywords – Measurement Tool, Generation Alpha, Aggressive Behavior Preferences